Sustainable Compassion Training: Integrating Meditation Theory With Psychological Science - Condon, Paul; Makransky, John (Frontiers in Psychology, 2020)
Meditation programs continue to proliferate in the modern world, with increasing participation from stakeholders throughout science and those who seek to improve physical, mental, relational, and social flourishing. In developing such programs, the meditation practices and contextual factors surrounding them have been adapted to meet the needs of modern cultures. However, in so doing, important contextual factors of traditional cultures are often dropped or forgotten. This article presents a system of compassion and mindfulness training, Sustainable Compassion Training (SCT), which is designed to help people cultivate increasingly unconditional, inclusive, and sustainable care for others. SCT aims to recover important contextual factors of meditation that flexibly meet the diverse needs of modern secular, and religious participants. SCT draws on Tibetan Buddhism in dialogue with caregivers, other contemplative traditions and relevant scientific theories to inform meditative transformation for secular contexts. We provide an overview of SCT meditations that includes both contemplative and scientific theories that draw out important features of them. Each meditation includes novel hypotheses that are generated from this dialogical process. We also provide links to audio-guided meditations.